Influence of opioid analgesia type on circulating tumor cells in open colorectal cancer surgery (POACC-1): study protocol for a prospective randomized multicenter controlled trial - Berta, Emil; Srovnal, Josef; Dytrych, Petr; Bruthans, Jan; Ulrichova, Jitka; Prasil, Petr; Vecera, Lubomir; Gabrhelik, Tomas; Tolmaci, Benjamin; Dusa, Josef; Maca, Jan; Mazancova, Michelle; et al. (BMC anesthesiology, 2023)
BACKGROUND: Opioids and epidural analgesia are a mainstay of perioperative analgesia but their influence on cancer recurrence remains unclear. Based on retrospective data, we found that cancer recurrence following colorectal cancer surgery correlates with the number of circulating tumor cells (CTCs) in the early postoperative period. Also, morphine- but not piritramide-based postoperative analgesia increases the presence of CTCs and shortens cancer-specific survival. The influence of epidural analgesia on CTCs has not been studied yet. METHODS: We intend to enroll 120 patients in four centers in this prospective randomized controlled trial. The study protocol has been approved by Ethics Committees in all participating centers. Patients undergoing radical open colorectal cancer surgery are randomized into epidural, morphine, and piritramide groups for perioperative analgesia. The primary outcome is the difference in the number of CTCs in the peripheral blood before surgery, on the second postoperative day, and 2-4 weeks after surgery. The number of CTCs is measured using molecular biology methods. Perioperative care is standardized, and relevant data is recorded. A secondary outcome, if feasible, would be the expression and activity of various receptor subtypes in cancer tissue. We intend to perform a 5-year follow-up with regard to metastasis development. DISCUSSION: The mode of perioperative analgesia favorably affecting cancer recurrence would decrease morbidity/mortality. To identify such techniques, trials with long-term follow-up periods seem suboptimal. Given complex oncological therapeutic strategies, such trials likely disable the separation of perioperative analgesia effects from other factors. We believe that early postoperative CTCs presence/dynamics may serve as a sensitive marker of various perioperative interventions´ influences on cancer recurrence. Importantly, it is unbiased to the influence of long-term factors and minimally invasive. Analysis of opioid/cannabinoid receptor subtypes in cancer tissue would improve understanding of underlying mechanisms and promote personalization of treatment. We are not aware of any similar ongoing studies. TRIAL REGISTRATION NUMBER: NCT03700411, registration date: October 3, 2018. STUDY STATUS: recruiting.
Keywords: Colorectal surgery; Humans; Circulating tumor cells; Cancer recurrence; epidurální analgezie; Perioperative analgesia; multicentrické studie jako téma; Morphine; Neoplastic Cells, Circulating; lidé; randomizované kontrolované studie jako téma; Epidural; Analgesics, Opioid; Analgesia, Epidural; kolorektální nádory; Randomized Controlled Trials as Topic; Colorectal cancer; Retrospective Studies; opioidní analgetika; nádorové cirkulující buňky; Piritramide; retrospektivní studie; morfin; lokální recidiva nádoru; prospektivní studie; Neoplasm Recurrence, Local; Multicenter Studies as Topic; Colorectal Neoplasms; Prospective Studies